The copyeditor's handbook : a guide for book publishing and corporate communications - Einsohn, Amy; Schwartz, Marilyn (Oakland, California : University of California Press, 2019)
"Unstuffy, hip, and often funny, The Copyeditor's Handbook has become an indispensable resource both for new editors and for experienced hands who want to refresh their skills and broaden their understanding of the craft of copyediting. This fourth edition incorporates the latest advice from language authorities, usage guides, and new editions of major style manuals, including The Chicago Manual of Style. It registers the tectonic shifts in twenty-first-century copyediting: preparing text for digital formats, using new technologies, addressing global audiences, complying with plain language mandates, ensuring accessibility, and serving self-publishing authors and authors writing in English as a second language. The new edition also adds an extensive annotated list of editorial tools and references and includes a bit of light entertainment for language lovers, such as a brief history of punctuation marks that didn't make the grade, the strange case of razbliuto, and a few Easter eggs awaiting discovery by keen-eyed readers. The fourth edition features updates reflecting the transformation of editorial roles in today's publishing environment, new applications, processes, and protocols for on-screen editing major changes in editorial resources, such as online dictionaries and language corpora, new grammar and usage authorities, online editorial communities, and web-based research tools. When you're ready to test your mettle, pick up The Copyeditor's Workbook: Exercises and Tips for Honing Your Editorial Judgment, the essential new companion to the handbook"--Provided by publisher
Preface to the fourth edition / Marilyn Schwartz -- Preface to the previous edition / Amy Einsohn -- Part 1. The ABCs of copyediting. What copyeditors do -- Basic procedures -- Reference books and resources -- Part 2. Editorial style. Punctuation -- Spelling and hyphenation -- Capitalization and the treatment of names -- Numbers and numerals -- Quotations -- Abbreviations and symbols -- Tables, graphs, and art -- References -- Front matter, back matter, and running heads -- Markup -- Part 3. Language editing. Grammar and usage : principles and pitfalls -- Beyond grammar.
Includes bibliographical references (pages 489-512) and index.
Print version record and CIP data provided by publisher; resource not viewed.
JSTOR
Keywords: Copy editing -- Handbooks, manuals, etc; Editing -- Handbooks, manuals, etc; Journalism, Commercial -- Editing -- Handbooks, manuals, etc; Copy editing; Révision de textes -- Guides, manuels, etc; Édition -- Guides, manuels, etc; Révision de textes; copyediting; LANGUAGE ARTS & DISCIPLINES -- Composition & Creative Writing; LANGUAGE ARTS & DISCIPLINES -- Rhetoric; REFERENCE -- Writing Skills; LANGUAGE ARTS & DISCIPLINES -- Editing & Proofreading; Copy editing; Editing; book publishing; business editor; chicago manual of style; citations; copyediter; copyediting; corporate communications; editing and revising; editors; footnotes; great handbook; onscreen editing; practical guide; publishing; resources for editors; student textbook; students and teachers; style guide; typecoding; writing students; writing teachers; Handbook; style manuals; handbooks; Style manuals; Handbooks and manuals; Handbooks and manuals; Style manuals; Guides et manuels; Codes typographiques